Self-supported nanoporous NiCo2O4 nanowires with cobalt–nickel layered oxide nanosheets for overall water splitting. Issue 3 (16th December 2015) - Yin, Jie; Zhou, Panpan; An, Li; Huang, Liang; Shao, Changwei; Wang, Jun; Liu, Hongyan; Xi, Pinxian
Abstract : We employed an efficient route for the synthesis of self-supported nanoporous NiCo2 O4 nanowires with cobalt–nickel layered oxide nanosheets (CFP/NiCo2 O4 /Co0.57 Ni0.43 LMOs) which can be used as bifunctional catalysts in both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). Abstract : Water splitting via the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in producing H2 and O2 is a very important process in the energy field. Developing an efficient catalyst which can be applied to both HER and OER is crucial. Here, a bifunctional catalyst, CFP/NiCo2 O4 /Co0.57 Ni0.43 LMOs, has been successfully fabricated. It exhibits remarkable performance for OER in 0.1 M KOH producing a current density of 10 mA cm −2 at an overpotential of 0.34 V (1.57 V vs . RHE), better than that of the commercial Ir/C (20%) catalyst. Simultaneously, it also exhibits good catalytic performance for HER in 0.5 M H2 SO4 producing a current density of 10 mA cm −2 at an overpotential of 52 mV and a Tafel slope of 34 mV dec −1, approaching that of the commercial Pt/C (20%) nanocatalyst. Particularly, CFP/NiCo2 O4 /Co0.57 Ni0.43 LMOs present better durability under harsh OER and HER cycling conditions than commercial Ir/C and Pt/C. Furthermore, an H-type electrolyzer was fabricated by applying CFP/NiCo2 O4 /Co0.57 Ni0.43 LMOs as the cathode and anode electrocatalyst, which can be driven by a single-cell battery. This bifunctional catalyst will be very promising in overall water splitting.